Vigilante Law Enforcement Eigenrichting Causing Death Through a Criminological Perspective - Perbaya, Alisma; Juhana, Ujuh (Journal La Sociale, 2025)
The phenomenon of vigilantism (eigenrichting) resulting in death reflects a failure in the formal legal system and the rise of revenge practices in society. This research uses a normative juridical method that focuses on the analysis of positive legal norms. Data were collected from various written sources, including legislation, court decisions, legal doctrine, legal theories, and the views of legal experts. The analysis was conducted qualitatively using a descriptive approach to interpret the meaning and information contained in documents, media reports, and newspaper archives. The analysis found that low legal understanding, socio-economic inequality, and a crisis of judicial legitimacy are the main triggers for vigilante behavior. The impacts are clear: loss of life, weakened public trust in legal institutions, and increased social insecurity. Recommendations include transparent and professional law enforcement, early legal education, improving socio-economic conditions, and implementing restorative justice principles to prevent revenge-based violence.